Paternal coping and psychopathology during the perinatal period: A mixed studies systematic review and meta-analysis. (June 2021) - Livingston, Julianne D.; Youssef, George J.; StGeorge, Jennifer; Wynter, Karen; Dowse, Eileen; Francis, Lauren M.; Di Manno, Laura; Teague, Samantha; Demmer, David; Collins, Sam; Wilford, Emily; Leach, Liana; et al.
Abstract: How fathers cope with stress may be critical to their mental health during the perinatal period. Using a sequential explanatory design for systematic review and meta-analysis, we aimed to identify associations and causal relations between higher- and lower-order avoidant and approach coping strategies and paternal psychopathology. We searched five electronic databases and grey literature, and used random-effects models to calculate pooled effects from 11 quantitative studies. Meta-analytic results were integrated with findings from 18 qualitative studies. Fathers' avoidant coping was positively associated with global psychopathology and depression. Approach-oriented coping, particularly problem-solving, was associated with positive affect but not psychopathology. Qualitative findings indicate distressed fathers employ avoidant coping strategies such as suppression, distraction, and social withdrawal. Approach-oriented coping strategies such as problem-solving and cognitive reappraisals appeared to be constructive components of men's coping repertoires supporting adaptation to fatherhood. Different coping strategies and approaches may reflect enactment of constrictive, moderate, or reinterpreted masculine norms. Study designs did not allow conclusions about causal relations between coping and psychopathology. Screening for, and targeting of, high avoidant coping among expectant and new fathers may help detect men at risk of or experiencing mental health difficulties and inform clinical response to psychopathology. Research examining whether different patterns of avoidant and approach coping are associated with psychopathology over time could inform interventions to support men's mental health and adaptation to fatherhood. Highlights: Avoidant coping was associated with global psychopathology and depressive symptoms. Approach coping, specifically problem-solving, was associated with positive affect but not psychopathology. Approach coping strategies may be important components of broader coping repertoire. Masculine norms appear to influence paternal coping during the perinatal period.